The Diagnostic Frame in National Security Evaluations. Issue 6 (9th July 2019) - Smith, Kim
Abstract: In clinical and most forensic evaluations, "diagnosis" connotes the expectation of a DSM‐5 or ICD‐10 formally labeled mental condition. When the task is to evaluate the security risk a person's psychological makeup presents to an institution, such a molar diagnosis can blind the clinician and elevate the risk to a security agency. When "diagnosis" connotes achieving an understanding of a person's behavior that has raised security concerns, then a different conceptualization of the diagnostic process is required. Unlike the clinical situation, the evaluation is not being performed to benefit the person but for the purpose of assessing risk to an agency. The differences this introduces involve every aspect of the evaluation and changes the type of diagnosis expected. Not appreciating these differences can cause the clinician to fail in the task of assessing psychological tendencies that affect national security.